Mutagen resistance and mutation restriction of St. Louis encephalitis virus - Griesemer, Sara B (J Gen Virol, 2017)
The error rate of the RNA-dependent RNA polymerase (RdRp) of RNA viruses is important in maintaining genetic diversity for viral adaptation and fitness. Numerous studies have shown that mutagen-resistant RNA virus variants display amino acid mutations in the RdRp and other replicase subunits, which in turn exhibit an altered fidelity phenotype affecting viral fitness, adaptability and pathogenicity. St. Louis encephalitis virus (SLEV), like its close relative West Nile virus, is a mosquito-borne flavivirus that has the ability to cause neuroinvasive disease in humans. Here, we describe the successful generation of multiple ribavirin-resistant populations containing a shared amino acid mutation in the SLEV RdRp (E416K). These E416K mutants also displayed resistance to the antiviral T-1106, an RNA mutagen similar to ribavirin. Structural modelling of the E416K polymerase mutation indicated its location in the pinky finger domain of the RdRp, distant from the active site. Deep sequencing of the E416K mutant revealed lower genetic diversity than wild-type SLEV after growth in both vertebrate and invertebrate cells. Phenotypic characterization showed that E416K mutants displayed similar or increased replication in mammalian cells, as well as modest attenuation in mosquito cells, consistent with previous work with West Nile virus high-fidelity variants. In addition, attenuation was limited to mosquito cells with a functional RNA interference response, suggesting an impaired capacity to escape RNA interference could contribute to attenuation of high-fidelity variants. Our results provide increased evidence that RNA mutagen resistance arises through modulation of the RdRp and give further insight into the consequences of altered fidelity of flaviviruses.